Inherently safer chemical processes : a life cycle approach (Center for Chemical Process Safety ; Wiley, 2009)
Inherently Safer Chemical Processes presents a holistic approach to making the development, manufacture, and use of chemicals safer. It discusses strategies for substituting more benign chemicals at the development stage, minimizing risk in the transportation of chemicals, using safer processing methods at the manufacturing stage, and decommissioning a manufacturing plant. Since the publication of the original concept book in 1996, there have been many developments on the concept of inherent safety. This new edition provides the latest knowledge so that engineers can derive maximum bene.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books